Changes in sonoelastography indices of stiffness as a criterion of evaluation of efficiency of neoadjuvant chemotherapy for breast cancer - E. A. Bus'ko; T. Yu. Semiglazooa; V. V. Klimenko; A. V. Komiyakhoo; A. V. Mshchenko; V. V. Serniiglazoo (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
The purpose of this study was to evaluate the capabilities of sonoelastography to monitor neoadjuvant chemotherapy of breast cancer and to determine correlation between reduction of stiffness of the tumor and the grade of pathology response.